2019
DOI: 10.4018/ijcrmm.2019070103
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Usage of Smartphone Media Technologies as A Source of News by Egyptian University Students

Abstract: This study examines the adoption and use of smartphones as a source of news by Egyptian university students. The study was applied on a random sample of 400 university students, whom already have smartphones. This study was guided by the uses and gratification theory to explore the use of smartphones among university students as a news resource. The study used quantitative research methodology in the form of a survey. Information was collected using a self-administrated questionnaire between March 2018 and Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The present result showed that approximately 80% of respondents used smartphones either alone or in combination with other Internet‐ready electronic devices in their online learning during the pandemic lockdown. This result passes in line with that of Saad (2019), who reported that the majority of the Egyptian university students are heavy smartphone users. About 93% and 50% of the total population in Egypt have mobile connections and a mobile Internet connection, respectively (Kibuacha, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The present result showed that approximately 80% of respondents used smartphones either alone or in combination with other Internet‐ready electronic devices in their online learning during the pandemic lockdown. This result passes in line with that of Saad (2019), who reported that the majority of the Egyptian university students are heavy smartphone users. About 93% and 50% of the total population in Egypt have mobile connections and a mobile Internet connection, respectively (Kibuacha, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Smartphones have also become the most important devices used to access the news among universitystudentsintheGCC (Zayani,Elareshi&Gunter,2015).AccordingtoKatzandAakhus (2002)universaluseofsmartphonesamonggroupsofcommunities,suchasuniversitystudentshas reshapedandrevolutionizedthewayyoungadultsandvariousgroupscommunicate.Furthermore, Saad(2018)examineduniversitystudents'usageofsmartphonesasanewsresourceinEgyptand revealedthatmostuniversitystudentsinEgyptareheavysmartphoneusersandthevastmajority (87.5%)ofthemareaccessingnewsviatheirsmartphones.AccordingtotheArabYouthSurvey (2016),socialmediacontributestothewayArabyoungadultsaccessthenews,as32%saidthey would get daily news electronically, 29% would watch TV, and 7% would read newspapers. The applicationWhatsAppisconsideredasthemostpopularsocialnetworkingplatformforArabyoung adults,giventhat2of3people(62%)useitdaily,followedbyFacebook(55%),YouTube(33%), Twitter(28%)andInstagram(28%)("ArabYouthSurvey",2016).Thesefindingsclearlyindicate thatsmartphonedevicesaregaininganincreasedpopularityasanewsresource,especiallybyyoung adultsintheArabregion.…”
Section: Smartphones and News Consumptionmentioning
confidence: 99%